The The demand for a professional identity of school principals in Spain: development and barriers - Bolívar Botía, Antonio (Avances en Supervisión Educativa, 2024)
Effective educational leadership in schools, across the board, requires the recognition of a professional identity of school leadership. In this article we intend to review the lack of identity and professionalism, as well as the efforts that our team, together with the Professional Associations of school leaders (FEDADI, FEDEIP) and Education Administrators (FEAE) have made in the last decades. Likewise, a critical analysis of the obstacles that have arisen and of the timid decisions taken by educational policies. This leads to a critical questioning of whether we really want professionalism in school principals.